A method, material and application for improving storage stability of solid electrolyte material

By covering the hydrophobic polymer layer on the surface of the solid lithium battery electrolyte material, the problem of water absorption in the solid electrolyte material during storage is solved, extending the shelf life of the material and reducing costs.

CN114421023BActive Publication Date: 2025-02-18LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210062574.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-19
Publication Date
2025-02-18
Estimated Expiration
2042-01-19

AI Technical Summary

Technical Problem

The solid electrolyte materials in solid-state lithium batteries are prone to water absorption, resulting in an increase in moisture content during storage, affecting the internal resistance and cycle life of the battery.

Method used

A hydrophobic polymer layer is prepared on the surface of the solid electrolyte material, and a continuous film is formed through polyvinylidene fluoride and/or polytetrafluoroethylene material to isolate contact with moisture in the environment.

Benefits of technology

Effectively control the water absorption of solid electrolyte materials, reduce the humidity requirements of storage environment, extend the shelf life of the materials, and reduce storage and use costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114421023B_ABST
    Figure CN114421023B_ABST
Patent Text Reader

Abstract

The present invention discloses a method, material and application for improving the storage stability of solid electrolyte materials, including: preparing a polymer layer on the surface of the solid electrolyte material; the material forming the polymer layer includes: polyvinylidene fluoride and / or polytetrafluoroethylene. The method for improving the storage stability of the solid electrolyte material of the present invention is to coat the surface of the solid electrolyte material with a layer of hydrophobic polymer to isolate it from contact with moisture in the environment, so that the whole material can maintain a low moisture state for a long time, so that the storage and use costs of the solid electrolyte material are lower, and the shelf life of the solid electrolyte material is extended.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material technology, and in particular to a method, material and application for improving the storage stability of a solid electrolyte material. Background Art

[0002] Lithium-ion battery is a secondary battery that mainly relies on the movement of lithium ions between the positive electrode and the negative electrode to work. + Insertion and deinsertion back and forth between the two electrodes: During charging, Li + It is deintercalated from the positive electrode and intercalated into the negative electrode through the electrolyte, and the negative electrode is in a lithium-rich state; the opposite is true during discharge.

[0003] At present, the rapid development of new energy vehicles, large-scale energy storage power stations and micro devices has put forward higher requirements on the energy density, power density, working environment and safety of secondary batteries. Therefore, solid-state lithium batteries, as the most promising electrochemical energy storage device, have received extensive attention and research in recent years.

[0004] Solid-state batteries use solid electrolytes to replace the liquid organic electrolytes in the original liquid lithium-ion batteries. Since the organic components in the liquid organic electrolyte are hydrophobic components, they can control the absorption of water, so there is no need to worry too much about water absorption during storage. However, solid electrolytes are easy to absorb water because they contain hydrophilic groups, and because the solid electrolyte powder has a small particle size, its specific surface area is large and it is easy to adhere to water. In addition, the pore structure of the solid electrolyte powder will also absorb water, causing the moisture content of the solid electrolyte to increase during storage.

[0005] Lithium-ion batteries contain a relatively complex chemical system. The reaction processes and results of these chemical systems are closely related to water. Water is brought into the battery through solid electrolytes, which will affect the battery's internal resistance, cycle life, etc., thereby affecting the performance of lithium-ion batteries. Therefore, it is necessary to find a reliable method to control the solid electrolyte to adsorb moisture in the storage environment to avoid absorbing moisture during storage and affecting battery performance. Summary of the invention

[0006] The embodiments of the present invention provide a method, material and application for improving the storage stability of solid electrolyte materials. By coating the surface of the solid electrolyte material with a layer of hydrophobic polymer, the solid electrolyte material is isolated from contact with moisture in the environment, so that the whole material can maintain a low moisture content for a long time, thereby reducing the storage and use costs of the solid electrolyte material and extending the shelf life of the solid electrolyte material. The present invention uses a method for improving the storage stability of a solid electrolyte material to obtain a solid electrolyte material having a surface coated with a polymer layer. During use, the surface polymer can be dissolved and can be used as a binder, and will not cause adverse effects on the electrochemical properties of the electrolyte itself.

[0007] In a first aspect, an embodiment of the present invention provides a method for improving the storage stability of a solid electrolyte material, the method comprising: preparing a polymer layer on the surface of the solid electrolyte material;

[0008] The material forming the polymer layer includes: polyvinylidene fluoride and / or polytetrafluoroethylene.

[0009] Preferably, the solid electrolyte material comprises: a mixture of one or more of a garnet-type solid electrolyte material, a NASCION-type solid electrolyte material, a LISCION-type solid electrolyte material, a perovskite-type solid electrolyte material or a sulfide solid electrolyte material.

[0010] Preferably, the mass ratio of the solid electrolyte particles to the polymer layer is 1:0.005-1:0.3; the particle size of the solid electrolyte material is between 10 nm and 30 μm, and the thickness of the polymer layer is between 1 nm and 2 μm.

[0011] Preferably, the polymer layer is a continuous film.

[0012] In a second aspect, a method for preparing a polymer layer on the surface of the solid electrolyte material as described in the first aspect above specifically comprises:

[0013] Weigh the solid electrolyte material and the polymer material in proportion, mix them evenly, and obtain a raw material complex; the polymer material includes: polyvinylidene fluoride and / or polytetrafluoroethylene;

[0014] The raw material complex is placed in a heat treatment device, heated to 120°C-600°C at a rate of 0.5°C / min-10°C / min, kept warm for 0.25 hours-10 hours, and then cooled to room temperature, to obtain a solid electrolyte material with a polymer layer coated on the surface.

[0015] Preferably, the solid electrolyte material comprises: a mixture of one or more of a garnet-type solid electrolyte material, a NASCION-type solid electrolyte material, a LISCION-type solid electrolyte material, a perovskite-type solid electrolyte material or a sulfide solid electrolyte material.

[0016] Preferably, the mixing method includes any one of stirring mixing, high-speed dispersing mixing, ultrasonic oscillation mixing, ball milling mixing or grinding mixing;

[0017] The heat treatment equipment includes: any one of a box furnace, a rotary furnace, a tube furnace, a push plate furnace, and a roller furnace.

[0018] In a third aspect, an embodiment of the present invention provides a solid electrolyte material having a polymer layer coated on its surface obtained by the method for improving the storage stability of a solid electrolyte material as described in the first aspect above; the water content of the solid electrolyte material having a polymer layer coated on its surface increases by less than 500 ppm after being stored in a 75% humidity environment for 30 days.

[0019] In a fourth aspect, an embodiment of the present invention provides a diaphragm, wherein the diaphragm comprises the solid electrolyte material having a surface coated with a polymer layer as described in the third aspect above.

[0020] In a fifth aspect, an embodiment of the present invention provides a lithium battery, wherein the lithium battery comprises the separator described in the fourth aspect.

[0021] A method for improving the storage stability of a solid electrolyte material provided by an embodiment of the present invention is to coat the surface of the solid electrolyte material with a layer of hydrophobic polymer to isolate it from contact with moisture in the environment, so that the whole material can maintain a low moisture state for a long time, thereby reducing the storage and use costs of the solid electrolyte material and extending the shelf life of the solid electrolyte material. The present invention uses a method for improving the storage stability of a solid electrolyte material to obtain a solid electrolyte material having a surface coated with a polymer layer. During use, the surface polymer can be dissolved and can be used as a binder, and will not cause adverse effects on the electrochemical properties of the electrolyte itself. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.

[0023] Figure 1 is a flow chart of a method for preparing a polymer layer on the surface of a solid electrolyte material provided by an embodiment of the present invention;

[0024] Figure 2 is a scanning electron microscope (SEM) image of a solid electrolyte material having a polymer layer coated on its surface provided in Example 1 of the present invention;

[0025] Figure 3 is a comparison diagram of particle size distribution curves of the solid electrolyte material provided in Example 2 of the present invention before and after being coated with a polymer;

[0026] Figure 4 It is a comparison chart of the X-ray diffraction patterns (XRD) of the solid electrolyte material provided in Example 3 of the present invention before and after being coated with the polymer. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.

[0028] An embodiment of the present invention provides a method for improving the storage stability of a solid electrolyte material, the method comprising: preparing a polymer layer on the surface of the solid electrolyte material;

[0029] The material forming the polymer layer includes: polyvinylidene fluoride and / or polytetrafluoroethylene; the polymer layer is a continuous film.

[0030] The solid electrolyte material includes: a mixture of one or more of garnet-type solid electrolyte material, NASCION-type solid electrolyte material, LISCION-type solid electrolyte material, perovskite-type solid electrolyte material or sulfide solid electrolyte material.

[0031] The mass ratio of the solid electrolyte particles to the polymer layer is 1:0.005-1:0.3; the particle size of the solid electrolyte material is between 10nm-30μm, and the thickness of the polymer layer is between 1nm-2μm.

[0032] An embodiment of the present invention provides a method for preparing a polymer layer on the surface of a solid electrolyte material according to the first aspect, and the specific steps include:

[0033] Step 110, weighing a solid electrolyte material and a polymer material in proportion, and mixing them evenly to obtain a raw material complex;

[0034] The solid electrolyte material includes: a mixture of one or more of a garnet-type solid electrolyte material, a NASCION-type solid electrolyte material, a LISCION-type solid electrolyte material, a perovskite-type solid electrolyte material or a sulfide solid electrolyte material;

[0035] The polymer material includes: polyvinylidene fluoride material and / or polytetrafluoroethylene material;

[0036] The mixing method includes any one of stirring mixing, high-speed dispersing mixing, ultrasonic vibration mixing, ball milling mixing or grinding mixing.

[0037] Step 120, placing the raw material complex in a heat treatment device, heating it to 120°C-600°C at a rate of 0.5°C / min-10°C / min, keeping it warm for 0.25 hours-10 hours, and then cooling it to room temperature, to obtain a solid electrolyte material with a polymer layer coated on the surface;

[0038] Among them, the water content of the solid electrolyte material coated with a polymer layer on the surface increases by less than 500ppm after being stored in a 75% humidity environment for 30 days. This is because the hydrophobic polymer coated on the surface of the solid electrolyte can effectively control the water absorption of the solid electrolyte, reduce the environmental humidity requirements for the storage of the solid electrolyte, and extend the shelf life of the material.

[0039] The heat treatment equipment includes: any one of a box furnace, a rotary furnace, a tube furnace, a push plate furnace, and a roller furnace.

[0040] An embodiment of the present invention provides a diaphragm, comprising a solid electrolyte material having a surface coated with a polymer layer obtained by the above method for improving the storage stability of a solid electrolyte material. The diaphragm can be used in a lithium battery.

[0041] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the solid electrolyte material having a polymer layer coated on the surface of the present invention are respectively described below with multiple specific examples.

[0042] Example 1

[0043] This embodiment provides a method for preparing a solid electrolyte material having a polymer layer coated on the surface, and the specific steps are as follows:

[0044] Weigh the NASICON solid electrolyte material Li with a particle size of 2 μm at a mass ratio of 1:0.06 1.2 Al 0.2 Ti 1.8 (PO4)3 and polyvinylidene fluoride are added into a stirrer and mixed thoroughly for 1 hour to obtain a raw material complex.

[0045] The raw material complex is placed in a box furnace, heated to 200°C at a rate of 2°C / min, kept warm for 5 hours, and then naturally cooled to room temperature to obtain a solid electrolyte material with a polymer layer coated on the surface.

[0046] Figure 2 The SEM of the solid electrolyte material with a polymer layer coated on the surface prepared in this embodiment shows that a layer of lamellar structure is attached to the surface of the solid electrolyte material, that is, the polymer layer coated on the surface of the solid electrolyte material.

[0047] Moisture content comparison test:

[0048] Test equipment: Calfisher moisture tester; Test conditions: 70% humidity, test sample moisture content before and after 30 days / 60 days at room temperature.

[0049] Test sample:

[0050] Sample 1#: NASICON solid electrolyte material Li without polymer coating used in this example 1.2 Al 0.2 Ti 1.8 (PO4)3;

[0051] Sample #2: a solid electrolyte material prepared in this embodiment with a polymer layer coated on the surface.

[0052] The test results are shown in Table 1

[0053] Example 2

[0054] This embodiment provides a method for preparing a solid electrolyte material having a polymer layer coated on the surface, and the specific steps are as follows:

[0055] The garnet-type solid electrolyte material Li7Ca3Ta2O with a particle size of 5 μm was weighed at a mass ratio of 1:0.1. 12 and polyvinylidene fluoride, add them into a ball mill and mix thoroughly for 1 hour until they are evenly mixed to obtain a raw material complex.

[0056] The raw material complex is placed in a tubular furnace, heated to 230°C at a rate of 2°C / min, kept warm for 4 hours, and then naturally cooled to room temperature to obtain a solid electrolyte material with a polymer layer coated on the surface.

[0057] Figure 3 The volume particle size distribution curve of the solid electrolyte material in this embodiment before and after being coated with the polymer. It can be seen from the figure that the average particle size D50 of the solid electrolyte after polymer coating is 6μm, and the average particle size D50 of the solid electrolyte material before being coated with the polymer is 5μm.

[0058] Moisture content comparison test:

[0059] Test equipment: Calfisher moisture tester; Test conditions: 75% humidity, test sample moisture content before and after 30 days / 60 days at room temperature.

[0060] Test sample:

[0061] Sample #3: The garnet-type solid electrolyte material Li7Ca3Ta2O used in this example without polymer coating 12 ;

[0062] Sample #4: a solid electrolyte material prepared in this embodiment with a polymer layer coated on the surface.

[0063] The test results are shown in Table 1

[0064] Example 3

[0065] This embodiment provides a method for preparing a solid electrolyte material having a polymer layer coated on the surface, and the specific steps are as follows:

[0066] Weigh the NASICON solid electrolyte material Li with a particle size of 2 μm at a mass ratio of 1:0.05 1.5 Al 0.5 Ti 1.5 (PO4)3 and polytetrafluoroethylene are added into a ball mill and mixed thoroughly for 1 hour to obtain a raw material complex.

[0067] The raw material complex is then placed in a tubular furnace, heated to 280°C at a rate of 2°C / min, kept warm for 2 hours, and then naturally cooled to room temperature to obtain a solid electrolyte material coated with a polymer layer on the surface.

[0068] Figure 4 This is the XRD diagram of the solid electrolyte material used in this embodiment before and after polymer coating. From the comparison of characteristic peaks in the figure, it can be seen that the polymer coating will not affect the structure of the original solid electrolyte material.

[0069] Moisture content comparison test:

[0070] Test equipment: Calfisher moisture tester; Test conditions: 60% humidity, test sample moisture content before and after 30 days / 60 days at room temperature.

[0071] Test sample:

[0072] Sample #5: NASICON solid electrolyte material Li 1.5 Al 0.5 Ti 1.5 (PO4)3;

[0073] Sample #6: a solid electrolyte material prepared in this embodiment with a polymer layer coated on the surface.

[0074] The test results are shown in Table 1

[0075] Example 4

[0076] This embodiment provides a method for preparing a solid electrolyte material having a polymer layer coated on the surface, and the specific steps are as follows:

[0077] The perovskite solid electrolyte material Li with a particle size of 3 μm was weighed at a mass ratio of 1:0.02. 0.33 La 0.557 TiO3 and polytetrafluoroethylene were added into a mortar and ground thoroughly for 0.5 hours and mixed evenly to obtain a raw material complex.

[0078] The raw material complex is then placed in a tubular furnace, heated to 200°C at a rate of 1°C / min, kept warm for 3 hours, and then naturally cooled to room temperature to obtain a solid electrolyte material coated with a polymer layer on the surface.

[0079] Moisture content comparison test:

[0080] Test equipment: Calfisher moisture tester; Test conditions: 75% humidity, test sample moisture content before and after 30 days / 60 days at room temperature.

[0081] Test sample:

[0082] Sample #7: The perovskite solid electrolyte material Li used in this example is not polymer coated. 0.33 La 0.557 TiO3;

[0083] Sample #8: a solid electrolyte material prepared in this embodiment with a polymer layer coated on the surface.

[0084] The test results are shown in Table 1

[0085] Example 5

[0086] This embodiment provides a method for preparing a solid electrolyte material having a polymer layer coated on the surface, and the specific steps are as follows:

[0087] Weigh the garnet-type solid electrolyte material Li7La3Zr2O with a particle size of 3 μm at a mass ratio of 1:0.02 12 and polyvinylidene fluoride, add them into a mortar and grind them thoroughly for 0.5 hours, mix them evenly, and obtain a raw material complex.

[0088] The raw material complex is placed in a tubular furnace, heated to 300°C at a rate of 3°C / min, kept warm for 3 hours, and then naturally cooled to room temperature to obtain a solid electrolyte material with a polymer layer coated on the surface.

[0089] Moisture content comparison test:

[0090] Test equipment: Calfisher moisture tester; Test conditions: Humidity 65%, test sample moisture content before and after 30 days / 60 days at room temperature.

[0091] Test sample:

[0092] Sample #9: The garnet-type solid electrolyte material Li7La3Zr2O used in this example without polymer coating 12 ;

[0093] Sample #10: a solid electrolyte material prepared in this embodiment with a polymer layer coated on the surface.

[0094] The test results are shown in Table 1

[0095] Table 1 is a table of test data of water content change of the solid electrolyte material and the solid electrolyte material coated with a polymer layer before and after being placed for 30 days / 60 days in Examples 1-5 of the invention;

[0096]

[0097] It can be seen from Table 1 that the water content increase data of the original solid electrolyte material in Examples 1-5 after being placed for 30 days / 60 days is much greater than the water content increase data of the solid electrolyte material coated with a polymer layer on the surface after being placed for 30 days / 60 days, indicating that the method of improving the storage stability of the solid electrolyte material of the present invention is effective. The method first volatilizes the water content of the solid electrolyte material itself under heat treatment conditions, and at the same time coats a layer of hydrophobic polymer on the surface of the solid electrolyte, so that the solid electrolyte material is isolated from the water in the environment, so that the solid electrolyte coated with a polymer on the surface reaches a state where low water content can be maintained for a long time, reduces the environmental humidity requirements for the storage of the solid electrolyte, makes the storage and use costs of the solid electrolyte material lower, and extends the shelf life of the solid electrolyte material.

[0098] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for improving the storage stability of a solid electrolyte material, characterized in that: The method comprises: preparing a polymer layer on the surface of the solid electrolyte material; The material forming the polymer layer includes: polyvinylidene fluoride and / or polytetrafluoroethylene; The method for preparing a polymer layer on the surface of the solid electrolyte material specifically comprises: Weigh the solid electrolyte material and the polymer material in proportion, mix them evenly, and obtain a raw material complex; the polymer material includes: polyvinylidene fluoride and / or polytetrafluoroethylene; The raw material complex is placed in a heat treatment device, heated to 120°C-600°C at a rate of 0.5°C / min-10°C / min, kept warm for 0.25 hours-10 hours, and then cooled to room temperature, to obtain a solid electrolyte material with a polymer layer coated on the surface; The mass ratio of the solid electrolyte material to the polymer layer is 1:0.005-1:0.3; The polymer layer is a continuous film; the thickness of the polymer layer is between 1 nm and 2 μm.

2. The method according to claim 1, characterized in that The solid electrolyte material includes: a mixture of one or more of a garnet-type solid electrolyte material, a NASCION-type solid electrolyte material, a LISCION-type solid electrolyte material, a perovskite-type solid electrolyte material or a sulfide solid electrolyte material.

3. The method according to claim 1, characterized in that The particle size of the solid electrolyte material is between 10 nm and 30 μm.

4. The method according to claim 1, characterized in that: The mixing method includes: stirring mixing, high-speed dispersion mixing, ultrasonic vibration mixing, ball milling mixing or grinding mixing; The heat treatment equipment includes: any one of a box furnace, a rotary furnace, a tube furnace, a push plate furnace, and a roller furnace.

5. A solid electrolyte material having a polymer layer coated on the surface obtained by the method for improving the storage stability of a solid electrolyte material according to any one of claims 1 to 4; After being stored for 30 days in a 75% humidity environment, the water content of the solid electrolyte material with the polymer layer coated on the surface increases by less than 500 ppm.

6. A diaphragm, characterized in that: The separator comprises the solid electrolyte material with a polymer layer coated on the surface as described in claim 5 above.

7. A lithium battery, characterized in that: The lithium battery comprises the separator according to claim 6.

Citation Information

Patent Citations

  • Super-hydrophobic material capable of conducting lithium ions as well as preparation method and application thereof

    CN112701345A